What a reckless rogue needs eaudiobook Sinful scoundrels series, book 2. - Dreiling, Vicky (Sinful Scoundrels, 2015)
"4 1/2 stars! TOP PICK! In the second of the Sinful Scoundrels series, Dreiling brings the Regency to life in a wonderfully evocative fashion. With believable, intelligent characters—including an honorable rake and a strong-willed lady—this moving tale, fraught with sexual tension, hits just the right notes." —RT Book Reviews on WHAT A RECKLESS ROGUE NEEDS WILL THE ROGUE'S PERFECT PLAN . . . Colin Brockhurst, Earl of Ravenshire, has no desire to wed, this season or any other. So when his father demands he give up his wild ways and take a wife, Colin refuses. But his father raises the stakes and threatens to sell the ancestral home if Colin doesn't comply. Now Colin has no choice but to find a wife. Unfortunately, the only woman he wants is the one whose heart he broke years ago. LEAD TO THE PERFECT SEDUCTION? Regardless of the ton's whispers, Lady Angeline Brenham won't settle for anything less than true love. After rejecting more than her share of suitable suitors, spinsterhood looms before her-until the devilishly handsome Colin reappears in her life with a proposition. Angeline vows to keep her feet on the ground and her heart in check. That is, until one searing kiss melts her resolve and reignites a burning desire for more . . .